2012
DOI: 10.1155/2012/472078
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of a Polypropylene Biocomposite Compounded with Maleated and Acrylated Compatibilizers

Abstract: Polypropylene (PP) biocomposites containing 20 wt.% sunflower hull as a particulate reinforcement were compounded and tested under tensile, flexural, and impact loadings. The incorporation of the sunflower hull without compatibilizer resulted in diminished tensile strength and impact energy absorption but increased flexural strength and both tensile modulus and flexural modulus when compared to neat PP. Formulations containing three different chemical compatibilizers were tested to determine their effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…FD values obtained in this study for samples PP‐ g ‐MHBP4, PP‐ g ‐MHBP5, and PP‐ g ‐MHBP6 (obtained with 9.0 wt % of MHBP) are higher than those reported by other authors, whose results were already mentioned earlier . The same occurs in the case of commercial samples of PP functionalized with MA, such as, Polybond 3200 (FD: 1.0 wt %), Polybond 3150 (FD: 0.50 wt %), G‐3003 (FD:1.2 wt %), E‐43 (FD:1.2 wt % ), Bondyran 1004 (FD:0.80 wt %).…”
Section: Resultssupporting
confidence: 59%
“…FD values obtained in this study for samples PP‐ g ‐MHBP4, PP‐ g ‐MHBP5, and PP‐ g ‐MHBP6 (obtained with 9.0 wt % of MHBP) are higher than those reported by other authors, whose results were already mentioned earlier . The same occurs in the case of commercial samples of PP functionalized with MA, such as, Polybond 3200 (FD: 1.0 wt %), Polybond 3150 (FD: 0.50 wt %), G‐3003 (FD:1.2 wt %), E‐43 (FD:1.2 wt % ), Bondyran 1004 (FD:0.80 wt %).…”
Section: Resultssupporting
confidence: 59%
“…The increase in flexural strength and modulus may be due to proper dispersion of the filler in the matrix and improved adhesion qualities in the case of biocomposites with compatibilizer. From the results, it is obvious that use of Ma‐ g ‐PP as a compatibilizer increased chemical bonding at the matrix‐fiber interface by eliminating weak boundary layers as explained elsewhere …”
Section: Resultsmentioning
confidence: 67%
“…Typically, a faster strain rate correlates to greater tensile strength in composites. This was supported by a study that found neat PP3825 had a strength of ~27 MPa and modulus of ~1.4 GPA when tested at a rate of 5 mm/min 32 . It appeared that BioC had poor bonding with the PP matrix, rendering it less efficient in stress transfer, as corroborated by other findings 2,11 .…”
Section: Results and Discussion Characterization Of Powder Samples Amentioning
confidence: 64%